Operation Control and Simulation of Supercritical Reheat Back Pressure Turbine - Honglei YUAN; Xinlong LIU; Xin LIU; Rongchao CHEN (南方能源建设, 2023)
[Introduction] In order to meet the needs of the rapid development of China's industry for high parameters and high-quality heat load, make full use of the advantages of the high efficiency of supercritical large-capacity units and the high thermal energy utilization rate of back pressure turbine generator units, it is necessary to develop and control the operation of supercritical reheat back pressure units. [Method] In this paper, on the basis of the research on the form and operation mode of the thermal system of the supercritical back pressure units, the control strategy under different operation conditions of the unit was proposed, and the simulation model of the turbine side of the supercritical reheat back pressure unit was established. [Result] The correctness of the control strategy is verified by the simulation of the key control strategy of the unit. [Conclusion] It lays a technical foundation for the engineering demonstration of supercritical reheat back pressure turbine technology and provides a reference for the heat supply transformation of the existing extraction-condensing units.